A prospective longitudinal study of voice characteristics and health-related quality of life outcomes following laryngeal cancer treatment with radiotherapy. (2nd June 2016) - Karlsson, Therese; Bergström, Liza; Ward, Elizabeth; Finizia, Caterina
Abstract: Background To investigate potential changes in perceptual, acoustic and patient-reported outcomes over 12 months for laryngeal cancer patients treated with radiotherapy. Material and methods A total of 40 patients with Tis-T3 laryngeal cancer treated with curative intent by radiotherapy were included in this prospective longitudinal descriptive study. Patients were followed pre-radiotherapy, one month, six months and 12 months post-radiotherapy, where voice recordings and patient-reported outcome instruments (European Organization for Research and Treatment of Cancer Quality-of-Life Questionnaire Core30, Head and Neck35, Swedish Self-Evaluation of Communication Experiences after Laryngeal Cancer) were completed at each appointment. Perceptual analysis, using the Grade-Roughness-Breathiness-Asthenia-Strain scale and vocal fry parameters, and acoustic measures including harmonics-to-noise ratio (HNR), jitter, shimmer and mean spoken fundamental frequency (MSFF) were produced from voice recordings. Results All patients presented with dysphonic voices pre-radiotherapy, where 95% demonstrated some degree of vocal roughness. This variable improved significantly immediately post-radiotherapy, however, then deteriorated again between six and 12 months. Vocal fry also increased significantly at 12 months. Acoustic measures were abnormal pre- and post-treatment with no significant change noted except for MSFF, which lowered significantly by 12 months. Health-related quality of life (HRQL) deteriorated post-radiotherapy but returned to pretreatment levels by 12 months. Conclusion By 12 months, most perceptual, acoustic, patient-reported voice and HRQL outcomes for laryngeal cancer patients treated by radiotherapy had showed no significant improvements compared to pretreatment function. Further studies are required to investigate potential benefits of voice rehabilitation following radiotherapy.